THE ADVANTAGES OF CHARACTER EDUCATION TO SUPPORT THE ONGOING ERA OF SOCIETY 5.0 IN HIGH SCHOOL STUDENTS - Pradwipta, Dhenok Aurorra Candra; Nugroho, Muhammad Irsyad Hamid; Alyafatin, Rafanida; Rivalianti, Astri; Haqq, Ahmad Zainul (Jurnal Penelitian Pendidikan Indonesia, 2025)
The Society 5.0 era demands education systems to produce graduates who are not only technologically proficient but also possess strong character, integrity, and adaptability. This article aims to analyze five key advantages of character education in preparing secondary school students to face the challenges of Society 5.0: enhancement of emotional and social intelligence, reinforcement of independence and responsibility, cultivation of ethical technology usage, development of adaptive and integrity-based youth, and promotion of ethical creativity and innovation. Using a descriptive qualitative method with observation and note-taking techniques, this study reveals that integrating character values comprehensively into the learning process helps shape students who are not only academically competent but also wise in using technology and upholding human values. Character education proves to be a strategic foundation for creating an excellent generation in this complex digital era.